2023
DOI: 10.1002/ldr.4902
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of the effects of ground‐based extraction technologies on fine roots in forest soils

Francesco Latterini,
Marcin K. Dyderski,
Paweł Horodecki
et al.

Abstract: Fine roots are an important component of forest soil as they play a key role in fundamental processes like plant nutrition and water supply. As with all the features of forest soil, the compaction related to the forest operations and, in particular, to the wood extraction via ground‐based technologies could lead to a significant impact on the presence of fine roots in the soil affected by the passage of the machines. Considering the lack of a review, we used a meta‐analytic approach to synthesise effect sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Due to the accelerated decomposition of litter on skid trails, there is an increased availability of nutrients in the soil, suggesting a possible positive effect on tree growth. However, it is important to consider the results of the meta-analysis by Latterini et al (2023), which showed that compacted soil on skid trails significantly hinders fine root growth. Consequently, improved nutrient availability may benefit tree growth only to a limited extent, as nutrients are less accessible to fine roots under compacted conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the accelerated decomposition of litter on skid trails, there is an increased availability of nutrients in the soil, suggesting a possible positive effect on tree growth. However, it is important to consider the results of the meta-analysis by Latterini et al (2023), which showed that compacted soil on skid trails significantly hinders fine root growth. Consequently, improved nutrient availability may benefit tree growth only to a limited extent, as nutrients are less accessible to fine roots under compacted conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on the effect of lateral displacement and water infiltration along ground-based operating trails-forwarding or skidding-have not been sufficient [8,10,13]. These disturbances associated with forest operations can have a significant impact on biological processes such as litter decomposition rates and fine root abundance, as shown in previous studies [14,15]. Therefore, it may be necessary to investigate the impact of ground-based based technologies on forest soils.…”
Section: Introductionmentioning
confidence: 97%
“…Logging operations are required to obtain wood for multiple purposes [5][6][7]. However, it is well known that logging operations can trigger substantial disturbance to the forest soil [3,[8][9][10][11][12][13]. Forest soils after logging are, indeed, in most cases, prone to compaction.…”
Section: Introductionmentioning
confidence: 99%